A relationship between unrecognized anaemia and the development of type 2 diabetes mellitus in patient with cardiovascular risks. (19th December 2020) - Choi, Byoung Geol; Kim, Jung Boone; Rha, Seung‐Woon; Kim, Suhng Wook; Lee, Min Woo; Lee, Michael S.; Choi, Se Yeon; Byun, Jae Kyeong; Cha, Jinah; Na, Jin Oh; Choi, Cheol Ung; Park, Chang Gyu; et al.
Abstract: Studies on anaemia in diabetic patients are well known. However, the data regarding association of anaemia on the development of diabetes mellitus (DM) are very limited. We aimed to evaluate the association of anaemia on the development of DM and major clinical outcomes in a series of the Korean population during 5‐year clinical follow‐up. The patients were retrospectively enrolled using the electronic database of Korea University Guro Hospital from January 2004 to February 2013. A total of 17 515 subjects without a history of DM were analysed. The World Health Organization definition of anaemia was used. Patients were divided into the anaemia group (n = 2907 patients) and the non‐anaemia group (n = 14 608 patients). The primary endpoint was the development of DM. To adjust baseline potential confounders, a propensity score matching (PSM) analysis was performed. After PSM analysis, two matched groups (2731 pairs) were generated and their baselines characteristics were balanced. During 5‐year follow‐up, the anaemia group had a higher incidence of type 2 DM (10.7% vs 7.7%; hazard ratio [HR], 1.356; 95% confidence interval [CI], 1.021–1.802; P = .035), and total death (2.6% vs 1.2%; HR, 2.449; 95% CI, 1.337–4.486; P = .004) compared to the non‐anaemia group. In the present study, anaemia was associated with higher rate of the development of DM and mortality during 5‐year clinical follow‐up. A randomized trial is needed to determine whether this results can be reproducible or not for the final conclusion. Abstract : Unrecognized anaemia can be an important risk factor for the development of type 2 diabetes mellitus in patients with cardiovascular risk and without diabetes. Therefore, in those populations, treatment, and prevention of diabetes and anaemia can be an important strategy for optimal treatment.